A single parameter determines mesophase transitions in Swollen Liquid Crystals. Issue 5 (8th April 2016) - Kinadjian, Natacha; Nallet, Frédéric; Ly, Isabelle; Bentaleb, Ahmed; Backov, Rénal; Prouzet, Eric
ABSTRACT: We report how the control of a single parameter, the co-surfactant, determines the phase transitions of oil-in-water swollen liquid crystals (SLCs) prepared with cetyltrimethylammonium bromide (CTAB), from cubic to hexagonal, lamellar, and finally sponge-like structures. SLCs are complex mixtures (surfactant + co-surfactant + water + salt + oil) usually prepared to form hexagonal mesophases, with cell parameters tunable between 3 and 30 nm. These hexagonal mesophases were successfully used as nanoreactors to prepare a broad range of nanostructured materials. Because the potential of these mesophases as adaptive nanoreactors has not been extended to other liquid crystal geometries than the hexagonal, we studied in a first step the structure evolution of SLCs made with CTAB, cyclohexane, pentanol-1, water and different stabilising salts. We used small-angle X-ray scattering (SAXS), polarised light microscopy and Freeze-Fracture TEM to provide a partial phase diagram and list the different mesophases obtained as a function of composition. We report that the adjustment of a single parameter, the co-surfactant (pentanol-1), determines the phase transition between cubic, hexagonal, lamellar, and sponge-like structures, all other parameters such as the nature and concentration of salt, or amount of oil being constant. GRAPHICAL ABSTRACT: